Efficacy and safety of oxaliplatin-based chemotherapy as first-line treatment in elderly patients with metastatic colorectal cancer: a meta-analysis - Fan, Shaoqing; Zhao, Zeming; Wang, Haiqian; Wang, Handong; Niu, Wenbo (Frontiers in Oncology, 2025)
PurposeThe global burden of colorectal cancer (CRC) continues to rise, with elderly populations disproportionately affected. Despite oxaliplatin’s established role in first-line metastatic CRC (mCRC) therapy, its clinical utility in older adults remains debated due to concerns over efficacy, toxicity, and survival outcomes. This meta-analysis evaluates the therapeutic benefits and risks of oxaliplatin-based regimens in elderly patients with mCRC, with emphasis on tumor response, survival endpoints, and treatment-related toxicities.MethodsWe systematically reviewed PubMed, Web of Science, Cochrane Library, and Chinese databases (CNKI, Wan Fang) through November 2024 for randomized controlled trials (RCTs) comparing oxaliplatin-based chemotherapy to non-oxaliplatin regimens in patients aged ≥65 with mCRC. Outcomes included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), complete response (CR), partial response (PR), disease control rate (DCR), and grade 3–4 adverse events. Data were pooled using random- or fixed-effects models in STATA 14.0 based on heterogeneity (I² statistic). Subgroup analyses explored heterogeneity sources, including chemotherapy combinations (e.g., bevacizumab, panitumumab).ResultsSeven RCTs (1,839 patients) met inclusion criteria. Oxaliplatin significantly improved tumor response rates versus control regimens: ORR (OR 2.18, 95% CI 1.75–2.72; P<0.001), CR (OR 2.57, 1.11–5.97; P=0.028), and PR (OR 1.69, 1.28–2.22; P<0.001). No significant survival benefit was observed for OS (HR 0.97, 0.86–1.08; P=0.58) or PFS (HR 0.90, 0.79–1.01; P=0.07), though trends favored oxaliplatin. Grade 3–4 neutropenia (RR 1.84, 1.32–2.57), diarrhea (RR 2.01, 1.45–2.78), and sensory neuropathy (RR 3.12, 1.98–4.91) were more frequent with oxaliplatin. Subgroup analysis attributed DCR heterogeneity (I²=66%) to regimen differences, with reduced variability in bevacizumab/pantiumumab-combined subgroups.DiscussionThis analysis demonstrates oxaliplatin’s capacity to enhance tumor response in elderly mCRC patients, potentially alleviating symptoms and improving quality of life. However, the absence of significant survival gains underscores the complex interplay between tumor biology and therapeutic resistance. Mechanistically, chemotherapy-driven clonal selection may favor residual resistant subpopulations, as evidenced by liquid biopsy studies linking tumor evolution to disease progression. While toxicity profiles were manageable, the elevated risk of neurotoxicity and myelosuppression necessitates vigilant monitoring in this vulnerable cohort.ConclusionOxaliplatin-based first-line therapy provides clinically meaningful tumor response improvements in elderly mCRC patients, though survival advantages remain elusive. Treatment decisions should balance response benefits against toxicity risks, prioritizing individualized strategies informed by geriatric assessments and molecular profiling. Future trials must integrate biomarker-driven approaches (e.g., ctDNA monitoring, RAS/RAF stratification) to optimize therapeutic precision in aging populations.